Transferências tendinosas para o tratamento de roturas maciças póstero-superiores da coifa: trapézio inferior vs. grande dorsal - João Vasco Sampaio Folhadela Simões (2021)
The massive postero-superior rotator cuff tears are an important cause of shoulder dysfunction. Its treatment is challenging, especially in young individuals who have a high functional demand. The aim of this work is to review the indications, contraindications, techniques and the results of two of the described techniques: the transfer of latissimus dorsi and lower trapezius. For this work was carried out a literature research through the databases of PubMed and Web of Science and were considered the articles published after 2015. Due to their particular relevance, some articles with a date before the defined were also included. Gerber described in 1988 the transfer of latissimus dorsi for the first time, showing good results in the improvement of pain and joint function, due to the robustness and wide excursion of this muscle. The transfer of lower trapezius was most recently described in 2016 by Elhassan. This technique has potential advantages in restoring glenohumeral kinematics because the muscle contracts synergistically with the external rotators of the shoulder ("in-phase" function), according to a traction line similar to the infraspinatus. The harvesting of its tendon is technically easier and faster, however, due to its shorter excursion, it is necessary to complete it with a graft. In selected cases of massive postero-superior rotator cuff tears, tendon transfers of latissimus dorsi or lower trapezius are valid and present good functional results, improving external rotation, frontal flexion and abduction. However, several factors regarding the choice of the technique and tendon must be considered, in order to offer the patient, the best outcome.